DISTRIBUSI GEOGRAFIS PENYAKIT GINJAL KRONIK DI BALI: KOMPARASI FORMULA COCKCROFT-GAULT DAN FORMULA MODIFICATION OF DIET IN RENAL DISEASE - Raka Widiana, I Gde (journal of internal medicine; Vol. 8, No. 3 September 2007, 2012)
Chronic kidney disease (CKD) is related to the increased of cardiovascular morbidity and mortality. This study is aiming to identify the prevalence of CKD based on demographical distribution in Bali. A community based study has been conducted in Bali, 1) height region among indigenous community in a village at northern part of Bali island using cluster random samples.; 2) in urban area at Denpasar city using stratified random sampling and 3) in isolated coastal area in Nusa Ceningan island using cluster random sampling. The glomerular filtration rate was calculated by Cockroft-Gault (C-G) formula and abbriviated Modification of Diet in Renal Disease ringkas with 4 variables (MDRD-4). The results of GFR using both calculation were compared. CKD was defined based on KDOQI classification, namely GFR less than 60 ml/mnt. During the study 826 samples were collected consisted of 219 from height region (males/females 118/101, aged 48±15 years, BW 48.9±10.4 kg, creatinine 0.97±0.64 mg/dL), 302 from urban area (males/females 137/165, aged 43±16 years, BW 56.1±12.1 kg, creatinine 0.81±0/.19 mg/dL) and 305 isolated coastal area (males/females 150/155, aged 42±16 years, BW 53.5±10.3 kg, creatinine 1.00±0.18 mg/dL). Using C-G, mean prevalence of CKD was 56.0% (95%CI 51.2-60.7%) consisted of 69.9% (95%CI 60.6-77.9%) in height region, 61.9% (95%CI54.5-68.8%) in urban and 42.3% (95%CI 33.7-51.4%) in isolated coastal area. Using 4-MDRD formula, mean prevalence of CKD was 6.0% ( 95%CI 1.4-18.2%) consisted of 4.8% (95%CI 0.00-31.2%) in height region, 2,6% (95%CI5 0.3-43.1%) in urban and 9.8% (95%CI 2.5-27.4%) in isolated coastal area. In conclusion, there is a significant difference of CKD prevalence in Bali if calculated by C-G compared with MDRD-4. Prevalence of CKD in Bali with MDRD-4 (6.0%) is similar to those in other countries such as USA (4.2%) and Thailand (8.8%). Whether the calculation of GFR using MDRD-4 is more accurate than C-G in this setting, needs further study.
Keywords: chronic kidney disease, Cockcroft-Gault, modification of diet in renal disease, prevalence